Investigative analysis of heavy metals in Oysters, Crasostrea sp. from Aklan River, Kalibo, Aklan. - Taytayon, Regie S. (2005.)
Metal concentrations in oysters, Crasostrea ap., with two different body sizes, collected from three sampling sites in Aklan River, Brgy. Bakhaw, Kalibo, Aklan, were investigated. The presence of Cadmium, Chromium, copper, Lead, Nickel and Tin were determined by flame atomic absorption spectrophotometry. The ranking of the average metal concentrations in the oyster samples was Sn> Cu> Pb> Cr> Ni> Cd. The overall average metal concentration, in mg metal/kg dry weight, in the soft tissue of oysters were 2.87 for Cadmium, 10.33 for Chromium, 202.93 for Copper, 22.19 for Lead, 5.93 for Nickel and 245.7 for Tin. The metal concentrations in the oyster samples were compared with the range for consumption set by the Joint FAO/WHO Expert committee on Food Additives (JECFA) and the Expert group on Vitamins and Minerals (EVM). Copper, Tin, and Lead concentrations in the oyster samples were above the tolerable limits of the safety guidelines, while Chromium, Nickel, and Cadmium were found to be within the tolerable range. Analysis of variance on the data showed significant differences in CU, Sn and Pb concentrations of the different body sizes of oysters, with smaller oysters having higher metal concentration than larger samples. There was no significant differences in the CR, CD, and Ni concentration; Cd and Ni concentrations among the samples are within the same range.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Oysters -- Heavy Metals -- Aklan River -- Kalibo, Aklan